Endogenous sex steroids and bone mineral density in healthy Greek postmenopausal women - Lambrinoudaki, I.; Christodoulakos, G.; Aravantinos, L.; Antoniou, A.; Rizos, D.; Chondros, C.; Kountouris, A.; Chrysofakis, G.; Creatsas, G. (Journal of Bone and Mineral Metabolism, 2006)
The aim of this study was to assess the association of endogenous sex steroids with bone mineral density (BMD) in healthy postmenopausal women not on hormone therapy. A total of 884 postmenopausal women aged 42-71 years were studied in a cross-sectional design. Parameters assessed were follicle-stimulating hormone, luteinizing hormone, estradiol, total testosterone, sex hormone-binding globulin, free estrogen index (FEI), free androgen index (FAI), Δ4-androstendione (Δ4A), dehydroepiandrosterone sulfate (DHEAS), bone alkaline posphatase, and bone mineral density at the lumbar spine (L-BMD) and femoral neck (N-BMD). Estradiol and FEI associated positively with both L-BMD and N-BMD (r = 0.21-0.47, P < 0.01). These associations remained significant after adjustment for age, years since menopause, and body mass index. FAI correlated positively with both L-BMD and N-BMD (r = 0.18 and 0.33, respectively; P < 0.01). At the multivariate analysis, however, FAI remained the significant determinant only for N-BMD. Δ4A associated positively with N-BMD (r = 0.27, P = 0.001), whereas DHEAS showed no association with BMD at either site. Thus, endogenous steroids are significant determinants of postmenopausal BMD. Endogenous estradiol may be more important for lumbar spine BMD, whereas endogenous androgens are associated mainly with femoral neck BMD. © Springer-Verlag Tokyo 2006.
Keywords: Androgen; Bone mineral density; Estrogen; Postmenopausal osteoporosis